Advertising in the Middle East: Exploring The Impact of the West - Sukkar, Mais; Pervan, Simon; Veer, Ekant (Indian Journal of Marketing, 2007)
With the global spotlight firmly on the Middle East, this paper sets out to investigate the influence the West has had on advertising content in the region. Using both in-depth interviews with industry professionals, as well as a survey of consumers, prevailing thoughts about Middle East culture are used to assess the nature of any change. Results indicate an acknowledgment of the impact from the West, though this is perceived as indirect; attributed to lifestyle rather than ad content. The implications being that there is still a need to communicate within a framework of Middle Eastern cultural values. Questions are also raised about the conflict between authentic tradition and modernity affecting the interpretation of results.